Strój kapłana w starożytnym Rzymie w czasach Oktawiana Augusta - Kaczmarek, Zofia (Studia Europaea Gnesnensia, 2010)
The article discusses issues surrounding vestments worn by priests in ancient Rome, during the reign of Octavian Augustus. The author attempts to prove that the attire was intimately associated with the office held, it highlighted the eminence, significance, function as well as distinguished the wearer. The matter is explored all the more easily thanks to the time span—the Augustan era—as the period offers numerous written and iconographic sources, as well as due to the fact that Augustus strove to reinstate traditional religion, its cults and priests.